Authentication of meat and dairy products using rare earth element labeling and detection by solution based and laser ablation ICP-MS. (June 2020) - Bandoniene, Donata; Walkner, Christoph; Ringdorfer, Ferdinand; Meisel, Thomas
Graphical abstract: Highlights: Lamb meat and goat milk can be labeled by spiking feed with rare earth elements. Rare earth element labeling can be used to assure the provenance of food products. Labels can be detected in the products using conventional or laser ablation ICP-MS. Abstract: In order to meet the increasing customer demand for local food products, various methods for verification of food origin by means of region specific trace element fingerprinting have been developed. However, for products from conventional agriculture, without a close relationship to the local soil, other methods for food authentication are required. In an alternative approach, foodstuffs produced in a certain region, by a specific producer or under certain conditions can be safeguarded against imitation by chemical labeling. The objective of the present study was to develop a method for labeling lamb meat and goat milk by selective enrichment of terbium and thulium in the feed for the animals. Therefore, a distinctive rare earth element (REE) pattern is artificially introduced which can be determined in labeled food products. Detection of REE labels was carried out using inductively coupled plasma mass spectrometry (ICP-MS) after acid digestion. Alternatively, laser ablation ICP-MS (LA-ICP-MS) was applied, allowing direct analysis of bone samples and analysis of meat and milk samples after dry ashing and pressing pellets. After three weeks of administering 1000-fold terbium and thulium enriched feed to lambs, terbium and thulium enrichment was detected in all sample types except blood, following the trend bones > kidney > liver > heart > meat > kidney fat. Similarly, goat milk was successfully labeled after three weeks of feeding 500-fold terbium and thulium enriched feed. Hence, the present method allows discrimination of labeled from unlabeled animal products, while REE contents in all labeled products remained low enough to avoid any health risk for the consumer.